'Let us go out to the Field': Apocalyptic Thinking in Christian Nationalism. (3rd July 2022) - Furse, Thomas
ABSTRACT: Christian nationalists attempt to save the United States from eternal damnation by forcefully confronting threats at home and abroad. This paper investigates how a selection of Christian nationalists in the US foreign policy-making ecosystem use the apocalypse to achieve their political aims. The 'strategic social construction' model demonstrates how and why the apocalyptic narrative is helpful to rally political action to halt the decline of the United States in the world order. It shows how it has justified their staunch criticism of domestic liberalism and can link them to extreme conspiratorial views while maintaining broad ties to mainstream politics. Through this overarching apocalyptic narrative, the working foreign policy objectives of Christian nationalism fit with the hegemonic orbit of liberal internationalism, which is flexible enough to encompass it. Thus, among elite US foreign policy-makers, the apocalypse has been a shared implicit and explicit frame of reference to interpret the US position in the world order in the twenty-first century.